Requirement Model for Small Agribusiness Web-Based Marketing System - Khalifa, Ibrahim Mohamed (2006)

(untitled)
The information and communication technology (ICT) provides a good channel to communicate information among businesses. By using this mean, information can be dispersed across geographical boundary and without time constraint. The major ICT applications such as email and web-sites allow businesses to expand their products to the larger market size. Email and web-site can be very cost effective product marketing strategy especially for small and medium enterprises (SME). This kind of marketing strategy has been implemented in various countries for various kinds of products and services. However, the implementation of web-based marketing for small agribusiness enterprises is quite new. This research is intended to discuss the requirement model for small agribusiness web-based marketing system.